2013
DOI: 10.1590/1983-21172013150303
|View full text |Cite
|
Sign up to set email alerts
|

Percepção De Professores Do Ensino Básico Em Relação as Suas Práticas Educativas Sobre Leishmanioses: Um Estudo Em Área Endêmica De Minas Gerais

Abstract: RESUMO:As leishmanioses têm alta prevalência no Brasil e, particularmente, em Divinópolis, Minas Gerais. O desconhecimento das enfermidades favorece sua disseminação. Por isso, este artigo apresenta uma investigação sobre a percepção de práticas educativas realizadas por professores de Ciências e Biologia do ensino básico quanto ao tema leishmaniose. Foram entrevistados dez docentes, e empregou-se o critério de saturação e a análise de conteúdo. Os resultados demonstraram que os professores atribuem pouca impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…A LV é uma manifestação mais recente, tendo sido registrado 15 casos da doença no mesmo período (13) . Estudos no município demonstraram desconhecimento da população e dos professores acerca das leishmanioses, verificando-se fragmentação do saber ao considerar o contexto científico da enfermidade (15,16) .…”
Section: Introductionunclassified
“…A LV é uma manifestação mais recente, tendo sido registrado 15 casos da doença no mesmo período (13) . Estudos no município demonstraram desconhecimento da população e dos professores acerca das leishmanioses, verificando-se fragmentação do saber ao considerar o contexto científico da enfermidade (15,16) .…”
Section: Introductionunclassified
“…The data found in the research from As well as other diseases, the knowledge about leishmaniasis is generally restricted to individuals who have experienced the disease or have had relatives or neighbors with the disease (UCHOA et al, 2004). A survey performed with teachers of basic education in the disciplines of biology and sciences about leishmaniasis demonstrated that they attach little importance to leishmaniasis, discuss the contents superficially together with the students because consider themselves unprepared (FRANÇA et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the primary education teachers, as they maintain a close contact with children and adolescents, can collaborate in transforming students into disseminators of the information received in the classroom. Study conducted in Divinópolis, Minas Gerais, regarding teacher's perception of leishmaniasis demonstrated that these professionals are not knowledgeable about this disease 37 , however, they are willing to raise awareness among their students, highlighting school as a favorable space to spread this knowledge 37 .…”
Section: Discussionmentioning
confidence: 99%